2011
DOI: 10.4271/2011-01-0160
|View full text |Cite
|
Sign up to set email alerts
|

The Bandwidth of Transient Yaw Effects on Vehicle Aerodynamics

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…At smaller angles, the elements act as lift devices, whilst at larger angles, the flow becomes separated and acts as a 1.4 The Unsteady Environment drag device. This approach attempts to bridge the gap between simulating longer and shorter length scales, although as stated by Mankowski et al (2011), it is the intermediate scales that still provide the greatest challenges.…”
Section: The Unsteady Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…At smaller angles, the elements act as lift devices, whilst at larger angles, the flow becomes separated and acts as a 1.4 The Unsteady Environment drag device. This approach attempts to bridge the gap between simulating longer and shorter length scales, although as stated by Mankowski et al (2011), it is the intermediate scales that still provide the greatest challenges.…”
Section: The Unsteady Environmentmentioning
confidence: 99%
“…Therefore transient aeroacoustic simulations are not currently widespread. This contrasts with transient force investigations, which, owing to their more moderate computational requirements are becoming more common, including those ofTsubokura et al (2010),Gaylard et al (2010) andMankowski et al (2011).…”
mentioning
confidence: 99%
“…Operating in this mode allows operation at up to 10 Hz with aerofoil amplitude continuously variable up to ±15°. Mankowski et al [29] showed that non-linearities in bluff body response mean that it is not sufficient to consider yaw harmonics individually and independently. Therefore incorporating programmed non-harmonic motion was important in the specification and implementation of the system.…”
Section: Methodsmentioning
confidence: 99%
“…[16]. On the contrary, the aerodynamic development of vehicles typically takes place in wind tunnels or with the use of CFD techniques assuming ideal conditions (e.g., uniform flow), thus introducing discrepancies vis-à-vis the actual aerodynamic performance of a vehicle driven on the road [17][18][19].…”
Section: Introductionmentioning
confidence: 99%